2016
DOI: 10.3892/etm.2016.4012
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and evaluation of an experimental rat model for high-altitude intestinal barrier injury

Abstract: In the present study an experimental high-altitude intestinal barrier injury rat model was established by simulating an acute hypoxia environment, to provide an experimental basis to assess the pathogenesis, prevention and treatment of altitude sickness. A total of 70 healthy male Sprague-Dawley rats were divided into two groups: Control group (group C) and a high-altitude hypoxia group (group H). Following 2 days adaptation, the rats in group H were exposed to a simulated 4,000-m, high-altitude hypoxia enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
(31 reference statements)
2
5
0
Order By: Relevance
“…(2017) who reported significant elevations in circulating endotoxins following exercise in normobaric hypoxia (14% FinormalO2${F_{{\rm{i}}{{\rm{O}}_{\rm{2}}}}}$), but not normoxia. Our data also confirm the findings of previous investigations demonstrating increased bacterial translocation following hypoxic exposures in rodent models (Luo et al., 2017; Q.‐Q. Zhou et al., 2011).…”
Section: Discussionsupporting
confidence: 92%
“…(2017) who reported significant elevations in circulating endotoxins following exercise in normobaric hypoxia (14% FinormalO2${F_{{\rm{i}}{{\rm{O}}_{\rm{2}}}}}$), but not normoxia. Our data also confirm the findings of previous investigations demonstrating increased bacterial translocation following hypoxic exposures in rodent models (Luo et al., 2017; Q.‐Q. Zhou et al., 2011).…”
Section: Discussionsupporting
confidence: 92%
“…While the risk of GI complications such as GI bleeding with ibuprofen use has been reported to be relatively low (32), this risk may be exacerbated by other contributing factors in the context of high-altitude. For example, rodent models have demonstrated that hypoxia alone can damage intestinal cells and increase intestinal permeability (33,34). While not assessed in the present study, the compounding effects of ibuprofen and hypoxia on intestinal barrier injury is an interesting area of study that may be relevant for high-altitude travel.…”
Section: Discussionmentioning
confidence: 99%
“…These changes can lead to mucosal barrier dysfunction. In addition, hypoxia can affect the intestinal mucosal immune system [49]. Low temperature can also affect the gut microbiome, which has a protective effect on obesity [50].…”
Section: Discussionmentioning
confidence: 99%